PERTANGGUNGJAWABAN PIDANA BAGI PELAKU MONEY LAUNDERING BERKEDOK INVESTASI MELALUI TRADING - Aniqoh, Ihda; Mahyani, Ahmad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Money laundering crimes often occur in parts of the world, including Indonesia. Money laundering is an activity in which a person keeps or does not reveal the origin of the proceeds of crime through various transactions so that the property appears to have originated from a legitimate act. Money laundering has 3 (three) stages, namely placement, layering and integration. Over time, money laundering can be done in any way, one of which is through investment or trading. This study uses a normative juridical method using statutory, conceptual and case approaches. This study discusses criminal responsibility for money laundering actors under the guise of investment through trading. The results of this study show that Decision Number 71/Pid.B/2022/PN Tbn. The judge decided to sentence the perpetrators of investment fraud through trading to imprisonment for 3 years and 8 months using the basis of Article 378 juncto Article 55 paragraph (1) 1 of the Criminal Code